The international positioning and impact of intermediary cities - Belil, Mireia (El posicionament i la incidència internacionals de les ciutats intermèdies, 2025)
"Intermediary cities play a key role in quality of life, innovation and development in their local communities, but they often face challenges in making their voice heard on the global stage. The study you hold in your hands analyses how these cities can overcome limitations in resources, knowledge or influence to project and position themselves in he international arena.